A practical solution to pseudoreplication bias in single-cell studies - Kip D. Zimmerman; Mark A. Espeland; Carl D. Langefeld (Nature Communications, 2021)
Single cell genomics uses cells from the same individual, or pseudoreplicates, that can introduce biases and inflate type I error rates. Here the authors apply generalized linear mixed models with a random effect for individual, to properly account for both zero inflation and the correlation structure among cells within an individual.